Kultura przedsiębiorstwa a zachowania innowacyjne - Penc, Józef (Wydział Prawa i Administracji UAM, 1990)
In his article the author discusses various aspects of innovative behaviour in an enterprise. He presents conditions favourable and detrimental to that process. A key to the succes of innovative behaviour in an enterprise in the creation of so-called innovative culture. In such culture, the strategy, organizational structure, economic processes and instruments, as well as the hierarchy of values, norms and behaviours, especially those of the management, are directed towards the support and activization of innovativeness. The formation of such culture is facilitated by certain principles, such as: accepting the necessity of innovations and making them the basis for the enterprise's existence, delimiting the areas of possible innovation, supporting creative employees and providing them with suitable technical, financial and organizational conditions, creating favourable climate for innovations, breaking down bureaucratic obstacles to their implementation, etc.
Innovative culture of an enterprise and innovative behaviours